Emergence of Blastoschizomyces capitatus Yeast Infections, Central Europe - Birrenbach, Tanja (Centers for Disease Control and Prevention, 2012)
We report 5 cases of disseminated infection caused by Blastoschizomyces capitatus yeast in central Switzerland. The emergence of this yeast in an area in which it is not known to be endemic should alert clinicians caring for immunocompromised patients outside the Mediterranean region to consider infections caused by unfamiliar fungal pathogens.